2007
DOI: 10.1016/j.bone.2006.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetics of cortical bone mass in healthy 10-year-old children from the Fels Longitudinal Study

Abstract: The genetic influences on bone mass likely change throughout the life span, but most genetic studies of bone mass regulation have focused on adults. There is, however, a growing awareness of the importance of genes influencing the acquisition of bone mass during childhood on lifelong bone health. The present investigation examines genetic influences on childhood bone mass by estimating the residual heritabilities of different measures of second metacarpal bone mass in a sample of 600 10-year-old participants f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…The lack of differences in body size parameters (weight, height, BMI) among robustness tertiles in the current study further suggested the biological processes regulating robustness are not easily related to those regulating body size. In fact, heritability estimates for metacarpal width are high, ranging from 64–72% after adjusting for cofactors such as sex, age, height, and weight [6, 15]. Prior work in inbred mouse strains identified quantitative trait loci (QTLs) harboring genes regulating bone length, periosteal circumference, and body weight individually, as well as QTLs harboring genes regulating the relationship among these traits [23].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of differences in body size parameters (weight, height, BMI) among robustness tertiles in the current study further suggested the biological processes regulating robustness are not easily related to those regulating body size. In fact, heritability estimates for metacarpal width are high, ranging from 64–72% after adjusting for cofactors such as sex, age, height, and weight [6, 15]. Prior work in inbred mouse strains identified quantitative trait loci (QTLs) harboring genes regulating bone length, periosteal circumference, and body weight individually, as well as QTLs harboring genes regulating the relationship among these traits [23].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 60 -80% of the variability in osteoporosis risk is explained by heritable factors (Krall and Dawson-Hughes 1993;Heaney et al 2000;Mora and Gilsanz 2003). Familial resemblance of BMC is expressed prior to puberty (Ferrari et al 1998;Duren et al 2007). Differences between population ancestry groups further demonstrate the strong genetic basis of variability in bone density and are evident in childhood (Gilsanz et al 1991;McCormick et al 1991;Bachrach et al 1999).…”
Section: Effects Of Genes and Behaviour On Bone Accretionmentioning
confidence: 93%
“…In doing so, we maximize the ability to detect genetic involvement in the study traits. Boys and girls were analyzed together in all genetic analyses (all bone measures were shown to have no significant differences between the sexes; Duren et al[9]).…”
Section: Methodsmentioning
confidence: 99%
“…Bone diameter, medial cortical thickness, lateral cortical thickness, and medullary diameter were each measured in millimeters on the second metacarpal (see Duren et al[9]). All measurements were taken directly from original radiographs using digital Mitutoyo calipers with direct computer input.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation